Yielding the Turn Strategies on Piers Morgan Vs Kari Lake Interview - Monica Heraldine Heraldine; Ambalegin Ambalegin (LPPM Universitas Putera Batam, 2023)
This research was proposed to discover conversation analysis especially from yielding the turn strategy by using the theory from (Stenstrom, 1994). This theory describes three strategies for yielding the turn, there are appealing strategy, prompting strategy, and giving up strategy. This research took the data source from Piers Morgan’s Uncensored YouTube video entitled “Piers Morgan vs Kari Lake”. For analyzing the data, this research used the qualitative method from Creswell (2013), since the researchers did not use statistics or numeric in collecting and analyzing the data. This research also used observational method from (Sudaryanto, 2015). In collecting and analyzing the data, this research used the theory identity method from (Sudaryanto, 2015). And for the data transcription, this research used transcription convention theory from (Paltridge, 2021). And it was found 12 data of yielding the turn strategies from conversation between Piers Morgan and Kari Lake in the YouTube video. Thus from 12 data, there are 6 data of appealing strategies, then there are 5 data of prompting strategies, and the last is 1 data of giving up strategies. Therefore, the most frequent data is showed by appealing strategy with 6 data, and the least is the giving up strategy with only found 1 data.